On (im)permeabilities: Social and human sciences on both sides of the 'Iron Curtain'. (October 2016) - Boldyrev, Ivan; Kirtchik, Olessia
While the history of Cold War social and human sciences has become an immensely productive line of inquiry and has generated some exciting research, a lot remains still to be done in studying more deeply the known stories, venturing into the unknown ones and, in particular, looking in greater detail at the Soviet side of the Iron Curtain. In our expository introduction to this special issue, we demonstrate how its articles enhance our understanding of the postwar social and human sciences. The special issue invites us to rethink the role of the local intellectual and disciplinary contexts in the postwar cultures of knowledge; to pay more attention to the networks and institutions that fostered communication across the Iron Curtain; to trace various asymmetries at work in the divided academic world and the ambiguous status of many actors who enable the East–West contacts despite the general hostility and ideological cleavages; and finally to arrive at a more differentiated and complex view of the whole intellectual landscape in the history of social and human sciences opening up once all the Cold War protagonists, including the countries of the eastern bloc, are subject to a detailed study. This project, we believe, is worthwhile not just for the sake of historical accuracy but also for understanding and changing the societies we live in, which are often still contaminated by the maladies of the Cold War.